Asymptomatic Bartholin Cyst: Evaluation With Multidetector Row Computed Tomography. Issue 1 (January 2018) - Silman, Christopher; Matsumoto, Shunro; Takaji, Ryo; Matsumoto, Akira; Otsuka, Ayumi; Mori, Hiromu; Nishida, Yoshihiro; Narahara, Hisashi; Ando, Tadasuke; Miyake, Hidetoshi
Abstract : Objective: The aim of this study was to determine the frequency, morphology, and attenuation characteristics of Bartholin cysts on multidetector computed tomography (MDCT) in asymptomatic women. Methods: A total of 3280 consecutive MDCT examinations were assessed for Bartholin cysts. The diagnosis was based on shape, contrast enhancement, and anatomical location. Age, laterality, size, and attenuation patterns were recorded. Scans from patients with paravaginal-related symptoms were excluded, and any available follow-up MDCT scans or magnetic resonance images were evaluated. Results: Asymptomatic Bartholin cysts were seen in 17 patients (0.52%) (mean age, 56 years). The mean maximum cyst diameter was 21.8 mm. High-attenuation cysts comprised 47% of cases, all in older (≥50 years) patients. Follow-up MDCT scans showed minimal changes over time. Conclusions: High-attenuation Bartholin cysts are more common than previously thought and are usually seen in older women. The size and attenuation of Bartholin cysts show only minimal changes over time.